2007
DOI: 10.1021/jp072681r
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Structure−Catalytic Activity Relationship for Pt−Co/C Bimetallic Nanoparticles toward the Oxygen Reduction Reaction

Abstract: Carbon-supported Pt−Co alloy nanoparticle catalysts of nominal atomic composition but with different alloying extents were prepared via a modified Watanabe process by employing microwave heating. Their structure was studied by X-ray diffraction (XRD) and X-ray absorption spectroscopy (XAS) techniques. Transmission electron microscopy (TEM) images indicated that the in-house-prepared Pt−Co alloy nanoparticles (sample-1 and sample-2) were well dispersed on the surface of the carbon support with narrow particle s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(73 citation statements)
references
References 50 publications
2
71
0
Order By: Relevance
“…Concerns like reducing the usage of noble metals have been considered to be major challenges in promoting the technology. To overcome such issues, some studies have reported that Pt-based alloys with transition metals (Co, [6] Ni, [7] Cr, [8] etc.) are helpful to improve the kinetics of the oxygen reduction reaction (ORR).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerns like reducing the usage of noble metals have been considered to be major challenges in promoting the technology. To overcome such issues, some studies have reported that Pt-based alloys with transition metals (Co, [6] Ni, [7] Cr, [8] etc.) are helpful to improve the kinetics of the oxygen reduction reaction (ORR).…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that the formation of Pt-skin alloys is caused by the dissolution of the base metal from Pt alloy under acidic conditions. [6,8,[15][16][17][18][19] Stamenkovic et al [19][20][21] have shown that the polycrystalline Pt 3 Co nanocrystal with a Pt-skin layer is more active than the polycrystalline Pt and bimetallic Pt 3 M surfaces (M = Fe, Ni, V, and Ti), because of the unusual electronic properties of the Abstract: The chemical dealloying mechanism of bimetallic Pt-Co nanoparticles (NPs) and enhancement of their electrocatalytic activity towards the oxygen reduction reaction (ORR) have been investigated on a fundamental level by the combination of X-ray absorption spectroscopy (XAS) and aberration-corrected scanning transmission electron microscopy (STEM). Structural parameters, such as coordination numbers, alloy extent, and the unfilled d states of Pt atoms, are derived from the XAS spectra, together with the compositional variation analyzed by line-scanning energy-dispersive X-ray spectroscopy (EDX) on an atomic scale, to gain new insights into the dealloying process of bimetallic PtCo NPs.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of ORR, the coverage of the adsorbed hydroxyl species (OH ad ) on the surface active sites will inhibit the O 2 adsorption and hinder the reaction. Upon the cyclic voltammetry (CV) curves of the catalysts, the Pt oxide oxidation peaks (0.8−1.0 V) have positive shifts relative to the Pt/C catalysts, suggesting that the PtCo 2 Ni 2 /C catalysts could promote the desorption of OH ad during ORR [52]. C600 catalyst shows the highest electrochemical surface area (ECSA) compared with other samples (Fig.…”
Section: Lettersmentioning
confidence: 98%
“…[13] The mass activity i m was then obtained via calculation of i k [Eq. (5)] and normalized with the weight of Pt used [Eq.…”
Section: Full Papermentioning
confidence: 99%
“…The number ofmetals in the alloy and the increase in particle size with respect to pure Pt. [13] The former problem occurs because the true alloy composition involving the 3d transition metal, which is difficult to reduce during synthesis, remains below the designed composition.…”
Section: Introductionmentioning
confidence: 99%